Controlling ratios of plasmid-based double cut donor and crispr/cas9 components to enhance targeted integration of transgenes in Chinese hamster ovary cells - Shin, Sung Wook; Kim, Dongwoo; Lee, Jae Seong (International Journal of Molecular Sciences, 2021)
Chinese hamster ovary (CHO) cells are the most valuable expression host for the commercial production of biotherapeutics. Recent trends in recombinant CHO cell-line development have focused on the site-specific integration of transgenes encoding recombinant proteins over random integration. However, the low efficiency of homology-directed repair upon transfection of Cas9, single-guide RNA (sgRNA), and the donor template has limited its feasibility. Previously, we demonstrated that a double-cut donor (DCD) system enables highly efficient CRISPR/Cas9-mediated targeted integration (TI) in CHO cells. Here, we describe several CRISPR/Cas9 vector systems based on DCD templates using a promoter trap-based TI monitoring cell line. Among them, a multicomponent (MC) system consisting of an sgRNA/DCD vector and Cas9 expression vector showed an approximate 1.5-fold increase in knock-in (KI) efficiency compared to the previous DCD system, when a systematically optimized relative ratio of sgRNA/DCD and Cas9 vector was applied. Our optimization efforts revealed that concurrently increasing sgRNA and DCD components relative to Cas9 correlated positively with KI efficiency at a single KI site. Furthermore, we explored component bottlenecks, such as effects of sgRNA components and applicability of the MC system on simultaneous double KI. Taken together, we improved the DCD vector design by tailoring plasmid constructs and relative component ratios, and this system can be widely used in the TI strategy of transgenes, particularly in CHO cell line development and engineering.
Keywords: Animals; CHO Cells; Cricetinae; Cricetulus; CRISPR-Cas Systems; Gene Editing; Gene Targeting; Plasmids; Recombinant Proteins; Transgenes; Chinese hamster ovary (CHO); CRISPR/Cas9; Double cut donor; Homology-directed repair; Multiple knock-in; Targeted integration; Vector construction